Turkish Workers' Party's Position on the Direction Revolutionary Movement - Khudhur ALJuboori, Firas Saleh; IBRAHIM AL-MAMOORI, SHATHA MOHAMMED (Journal of Tikrit University for Humanities, 2023)
The Turkish Workers' Party was distinguished from the rest of the socialist parties that emerged in Turkey in the aftermath of the 1960 coups, in that it adopted democratic methods and political action, a method to achieve the goals that the party tried to achieve, and moved away from revolutionary concepts that believed that change can only be achieved through adopting methods. The revolutionary methods to achieve the desired goals, and this is what made the party intersect in its political stances and adoptions with many socialist movements that appeared in Turkey during that era, which embraced and called for revolutionary methods. The research attempts to study the position of the Turkish Workers' Party on the revolutionary trend movement, although both of them adopted socialism as their political ideology. We find that both organizations had a path differed from the other, in terms of the nature of work and the method it adopted in achieving its goals. The research reached many results, the most important of which was that the Turkish Workers' Party was against the method of work and style of the revolutionary trend movement that believed in revolution, while the Turkish Workers' Party believed in democracy and its methods in achieving its goals.